Stimulation burn healing using 790 nm diode laser in rabbit’s skin - Mahmood, Ali S.; Meikha, Nadeem H. (The Iraqi Journal of Veterinary Medicine, 2009)
Burn is one of the most important conditions in veterinary and human medicine. The purpose of this study is to evaluate the enhancing therapeutic effect of 790 nm diode laser on the burn healing. Twenty-five rabbits (mean weight was 2.3 ± 0.03 kg) were divided into 5 groups (A, B, F, H and control group), each group consists of 5 animals. All groups were inflected with burn (scalds) by 99 degree of Celsius hot water applied for 30 seconds, on skin of the femoral region. Four groups were treated by laser and one group was without laser irradiation as a control group. The animals were treated by diode laser five times a week at different power density. The power density (PD) of 58.9 mW/cm² with exposure time 120 seconds was used for group (A), but in group (B), the same PD used with exposure time of 60 seconds, for group (F) the PD was 255mW/cm² and for group (H) the PD was 888 mW/cm² and same exposure time of 20 seconds for both last 2 groups. Results of four groups were compared with control group clinically and histopathologically. The study showed a good response in burn healing in (F) and (B) and (A) group, with no differences between group (H) and control group. The treatment of 5 times a week gave benefit in acceleration of the burn healing. The histological examinations revealed an increase in the proliferation of epithelial cells from the burn edge and decrease in the inflammatory cells infiltration in group F, B and A .The statistical results showed that the best results are